Fragmentation and molecular outflows in the IRDC core G34.43+00.24 MM1 - Isequilla, Natacha Laura (2021)
Massive star formation takes place in molecular hot cores which are the result of the fragmentation of massive clumps. The infrared dark cloud G34.43+00.24, which exhibits a filamentary structure, is located at a distance of about 3.6 kpc. This cloud harbours nine molecular cores, named MM1 through MM9, at different evolutionary stages. This work presents a study of the internal structure of the core MM1 carried out with high angular resolution observations at 93 GHz obtained from the ALMA database. The radio continuum emission shows signatures of fragmentation of the core, and the HCO+ J=l-0 emission confirms, with the better angular resolution at the present, the presence of two perpendicular molecular outflows arising from MM1.